Ustadz Musgianto Rafiq's Da'wah Method in the Routine Study of PDAM Tirtanadi Employees on the Development of Tauhid Values and Islamic Work Ethics - Yohani Putri Dinar; Nashrillah (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
This study aims to analyze Ustadz Musgianto Rafiq's da'wah methods in routine studies of PDAM Tirtanadi employees and their impact on fostering the values ​​of monotheism and Islamic work ethic. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that the da'wah methods used include lectures (bil-lisan), mau'izah hasanah, and interactive questions and answers. The material presented emphasizes strengthening monotheism and Islamic work ethic values ​​such as honesty, trustworthiness, and responsibility. These routine studies have a positive impact on increasing spiritual awareness and work motivation of employees within the company environment.